2020
DOI: 10.3390/su12176803
|View full text |Cite
|
Sign up to set email alerts
|

Research on Network Patterns and Influencing Factors of Population Flow and Migration in the Yangtze River Delta Urban Agglomeration, China

Abstract: Through the construction of a population flow and migration relationship matrix, this paper analyzes population flow and migration in the Yangtze River Delta urban agglomeration during the Spring Festival travel rush and daily period. This paper also studies the urban network spatial structure characteristics and the influencing factors from the perspective of inter-provincial population flow and migration. The results show the following: (1) as a central city, Shanghai has a significant siphon effect, with Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 25 publications
(22 reference statements)
1
18
2
Order By: Relevance
“…Thus the intensity of the mobility that is carried out will be higher so that it changes the pattern of mobility that is carried out [10]. Overall, the results of this study are very much in line with what Reivenstein said [11] and Wang et all [12], where the distance factor is the main determinant and conditional of people migrating.…”
Section: The Relationship Between Distances Length Of Stay Economic Conditions and Marital Status Of Migrants With The Intensity Of Mobilsupporting
confidence: 84%
“…Thus the intensity of the mobility that is carried out will be higher so that it changes the pattern of mobility that is carried out [10]. Overall, the results of this study are very much in line with what Reivenstein said [11] and Wang et all [12], where the distance factor is the main determinant and conditional of people migrating.…”
Section: The Relationship Between Distances Length Of Stay Economic Conditions and Marital Status Of Migrants With The Intensity Of Mobilsupporting
confidence: 84%
“…Compared with previous research results, the results of this paper show that the indicators of public ecology and information infrastructure have a strong ability to explain information flow [ 39 , 40 , 41 ]. For example, PGR, UPD, and CPM of public ecology increased by 1%; meanwhile, the information flow increased by 0.202%, 0.358%, and 0.215%, respectively.…”
Section: Discussioncontrasting
confidence: 69%
“…For example, the urban nodes in the central region of GPUA, such as Xi’an, Xianyang, Baoji, and Weinan, with closer geographical distance and superior location, quickly formed a cohesive subgroup. This feature can be explained in the research of Wu et al [ 40 ]: longer geographic distance will weaken the spread of information flow, while the information flow between neighboring cities has a strong agglomeration. The reason is that due to population migration, convenient transportation, and closer policy cooperation among neighboring cities, the information flow exchanges frequently.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Scholars' research has mainly revealed the spatial pattern and network characteristics of population mobility at the national level, and has drawn the conclusion that people prefer to be concentrated in major urban agglomerations and regional central cities with a hierarchical pattern [49][50][51], which preliminarily revealed the unbalanced relationship and asymmetrical characteristics of population mobility [6,52]. Meanwhile, population mobility patterns often show spatial differences in different scale units and regions [53].…”
Section: Spatial-temporal Heterogeneity Of Population Mobilitymentioning
confidence: 99%